(untitled) (UNED Research Journal, 2021)
Introduction: Due to its colors, shape, size, and simplicity of care, the neotropical fish Poecilia reticulata (guppy) is popular in the aquarium trade. It is also valued as mosquito control and is now found in most of the world. Objective: To report its presence in southern Mexico. Methods: Fish were captured with seine nets in a tributary of the Grijalva River, Chiapas, in August 2019, and March 2020. Results: Two hundred and fifty individuals of P. reticulata were captured. Conclusion: The species, found in México in 1971, has extended its range to the Grijalva Usumacinta river system.